2015
DOI: 10.1016/j.micres.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Phenazine-1-carboxylic acid mediated anti-oomycete activity of the endophytic Alcaligenes sp. EIL-2 against Phytophthora meadii

Abstract: The oomycete pathogen, Phytophthora meadii, causes various diseases in Hevea brasiliensis at different stages of its life cycle. The study reports the structural characterization of the active principle from the culture filtrate of Alcaligenes sp. EIL-2 (GenBank ID: HQ641257) offering antagonistic activity against P. meadii. Gas Chromatography Mass Spectroscopy (GC-MS) analysis showed the similarity of the compound with phenazine derivatives. The specific representations of FT-IR spectrum such as 3200 cm(-1) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Biosynthesis of phenazine‐derivatives has been well documented, particularly in the representatives of bacterial genus Pseudomonas 1–16. In addition to this, several other bacterial genera including Gram‐negative Sorangium, Alcaligenes, Brevibacterium , Burkholderia , Xanthomonas , and Gram‐positive genera such as Streptomyces, Nocardia and Bacillus have also been reported to be phenazine producers 12, 17–18. Out of 6000 phenazine containing compounds described so far, several hundred showed anti‐tumor, anti‐malarial and anti‐parasitic attributes 2.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Biosynthesis of phenazine‐derivatives has been well documented, particularly in the representatives of bacterial genus Pseudomonas 1–16. In addition to this, several other bacterial genera including Gram‐negative Sorangium, Alcaligenes, Brevibacterium , Burkholderia , Xanthomonas , and Gram‐positive genera such as Streptomyces, Nocardia and Bacillus have also been reported to be phenazine producers 12, 17–18. Out of 6000 phenazine containing compounds described so far, several hundred showed anti‐tumor, anti‐malarial and anti‐parasitic attributes 2.…”
Section: Introductionmentioning
confidence: 95%
“…Phenazine‐1‐carboxylic acid (PCA), also known as tubermycin B (due to its antibiotic activity against Mycobacterium tuberculosis ), is one simplest form of bacterial phenazines 12. PCA‐producing bacterial species have been regarded as effective biocontrol agents in agricultural applications, since they exhibit antagonism against diverse phytopathogenic fungi including the genus Aspergillus, Phytophthora, Alternaria, Rhizoctonia, Sclerotium, Colletoricum , Seiridium, Fusarium and Verticillium 3, 9–12, 17, 22. The antagonism is thought to be due to the redox behavior of PCA 1 which is a property that has also been exploited in the microbial fuel cells 4–5.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation between H-7 and C-8 also appears in the HMBC spectrum. All correlations showed that the isolated compound is phenazine-1carboxylic acid (PCA) (Abraham et al, 2015). This compound previously isolated from Streptomyces antibioticus strain Tü 2706 (Geiger et al, 1988), Pseudomonas aeruginosa (Jayatilake et al, 1996) and Pseudomonas aeruginosa UPMP3 (Lee et al, 2018) and Streptomyces kebangsaanensis (Remali et al, 2019).…”
Section: Resultsmentioning
confidence: 93%
“…PCA is known as an important broad-spectrum antimicrobial compound involved in the biocontrol of various plant pathogens, including Phytophthora spp. [ 22 , 24 , 32 ]. Generally, due to its nitrogen-containing heterocyclic composition, PCA is mainly described as promoting redox reactions and generating reactive oxygen species (ROS), of which the accumulation leads to a reduction in energy production, carbohydrate metabolism, and nutrient uptake [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%